Decision‐making process of prenatal screening described by pregnant women and their partners - Wätterbjörk, Inger (Health Expect, 2013)
BACKGROUND: Pregnant women are often faced with having to decide about prenatal screening for Down's syndrome. However, the decision to participate in or refrain from prenatal screening can be seen as an important decision not only for the pregnant woman but also for both the partners. OBJECTIVE: The aim of this study was to explore the couples' processes of decision making about prenatal screening. METHODS: A total of 37 semi‐structured interviews conducted at two time points were analysed using the interpretive description. SETTING: The study was carried out in Maternal health‐care centres, Örebro County Council, Sweden. PARTICIPANTS: Fifteen couples of different ages and with different experiences of pregnancy and childbirth were interviewed. RESULTS: Three different patterns of decision making were identified. For the couples in ‘The open and communicative decision‐making process’, the process was straightforward and rational, and the couples discussed the decision with each other. ‘The closed and personal decision‐making process’ showed an immediate and non‐communicative decision making where the couples decided each for themselves. The couples showing ‘The searching and communicative decision‐making process’ followed an arduous road in deciding whether to participate or not in prenatal screening and how to cope with the result. CONCLUSIONS: The decision‐making process was for some couples a fairly straightforward decision, while for others it was a more complex process that required a great deal of consideration.